ANALISIS NILAI TAMBAH HOME INDUSTRY TAHU DAN TEMPE DI KECAMATAN PURWODADI KABUPATEN GROBOGAN - Yoana Ariadani Manesa (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2020)
This research was purposed to analyze added value on tofu and tempeh home industry and analyze comparison of added value on tofu and tempeh home industry in Purwodadi District, Grobogan Regency. The method used in this research was survey with total of respondents is 11 tempeh home industry and 5 tofu home industry. The data analysis method used is descriptive analysis to find out an overview of the tofu and tempeh home industry and quantitative analysis using the Hayami and the Mann Whitney analysis test using SPSS. From the research, it is known that the process of making tempe takes longer, namely 3-4 days in one production time compared to the process of making tofu wich is only one day in one production. The added value of the tofu and tempeh home industry is classified as high, namely Rp. 64,800 / kg of soybeans and Rp. 37,300 / kg of soybeans, respectively, but the ratio of added value to the tofu home industry is 49.09%, relatively lower than the tempeh home industry of 74.6%. The results of the Mann Whitney test analysis on the added value of tofu and tempeh that there is a difference with a significance value of 0.000.